2017
DOI: 10.1007/s12650-017-0439-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of propeller-induced ground vortices by particle image velocimetry

Abstract: The interaction between a propeller and its self-induced vortices originating on the ground is investigated in a scaled experiment. The velocity distribution in the flow field in two different planes containing the self-induced vortices is measured by particle image velocimetry (PIV). These planes are a wall–parallel plane in close proximity to the ground and a wall–normal plane just upstream of the propeller. Based on the visualization of the flow field in these two planes, the occurrence of ground vortices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…Although the location of the propeller with respect to the wind-tunnel walls differed between the conventional and wingtip-mounted configurations, it was assumed that the propeller performance was the same for both cases. This is confirmed by previous work focusing on propeller aerodynamics in close ground proximity [14], which showed that propeller performance remains unaffected by wall spacing for spacing values above 1.5 times the propeller radius.…”
Section: Wing Modelssupporting
confidence: 88%
“…Although the location of the propeller with respect to the wind-tunnel walls differed between the conventional and wingtip-mounted configurations, it was assumed that the propeller performance was the same for both cases. This is confirmed by previous work focusing on propeller aerodynamics in close ground proximity [14], which showed that propeller performance remains unaffected by wall spacing for spacing values above 1.5 times the propeller radius.…”
Section: Wing Modelssupporting
confidence: 88%
“…However, these studies do not consider the presence of a rotor close to the wall. The experiments of Murray et al [21] show that, in that case, flow reversal can occur locally beneath the rotor and that additional unsteady vortical structures are formed, comparable to the ground-vortex effect encountered on propeller aircraft at low advance ratios [22]. Similar phenomena were observed in propeller-hull interaction studies [23,24].…”
Section: Introductionmentioning
confidence: 65%
“…These vortex/boundary-layer interaction studies do not consider the presence of a rotor close to the wall, which imposes additional pressure gradients and three-dimensional effects. The experiments of Murray et al [32] show that, in that case, flow reversal can occur locally beneath the rotor and that additional unsteady vortical structures are formed, which are comparable to the ground-vortex effect on propeller aircraft [33] or propeller-hull interaction effects in marine applications [34,35]. Moreover, if the tip clearance between the rotor and the wall is small, the local thrust increases not only due to the local reduction in inflow velocity, but also due to the end-plate effect [36].…”
Section: Experimental Investigation Of Over-the-wingmentioning
confidence: 98%